Racial disparity in renal cell carcinoma patient survival according to demographic and clinical characteristics1. Issue 2 (12th November 2012) - Chow, Wong‐Ho; Shuch, Brian; Linehan, W. Marston; Devesa, Susan S.
Abstract BACKGROUND: Patients with renal cell carcinoma (RCC) who are black tend to have poorer prognosis than similar patients who are white. This study examined whether the racial disparity in RCC patient survival varies by demographic and clinical characteristics. METHODS: Nearly 40, 000 patients (4359 black and 34, 991 white) diagnosed with invasive RCC from 1992 to 2007 were identified from 12 registries in the National Cancer Institute Surveillance, Epidemiology, and End Results program, covering approximately 14% of the US population. Relative survival rates through 2008 were computed using the actuarial method. RESULTS: Proportionally more blacks than whites were diagnosed with RCC under age 50 and with localized cancer. Overall, the 5‐year relative survival rates were 72.6% (95% confidence interval 72.0%‐73.2%) for white and 68.0% (66.2%‐69.8%) for black patients. Survival was higher among women than men and among younger than older patients. Survival decreased with advancing tumor stage and, within each stage, decreased with increasing tumor size. Patients with clear cell RCC, a more common form among whites, had poorer prognosis than patients with papillary or chromophobe subtypes, which are more common among blacks. Survival for patients who received no surgical treatment (10.5% of white patients and 14.5% of black patients) was substantially lower than for patients treated with nephrectomy, with similar survival among whites and blacks. In all other demographic and clinical subgroups of patients, whites consistently had a survival advantage over blacks. CONCLUSIONS: Patients with RCC who are white consistently have a survival advantage over those RCC patients who are black, regardless of age, sex, tumor stage or size, histological subtype, or surgical treatment. Cancer 2013. © 2012 American Cancer Society.